Caderno de leitura literária : a fabulação do leitor - Barboza, Rejanilza Santos da Silva (2015)
This Final Conclusion Work Dissertation comes from a design that seeks to value the fable process in the teaching of literature through intertextuality and literary text fruition. Our goal turns to the development of a literary reading book facing the interpretation of literary texts through the look of subjective reading, considering the creativity of the player at the reception process. For this, theoretical studies have been developed that make reference to the senses of the literary reading focused on the practice of subjectivity that involves a sensitive response and creative to literary reading based on A. Rouxel and in studies of some methodological approaches to literary text teaching of Brazilian researchers: R.Cosson and W.Cherry. We also explored the concepts developer player U. Eco, as a cooperative movement of the reader to construct directions. Finally, as methodological procedures and instruments, both were adopted as bibliographic perspective on qualitative from a proposal for literary workshops held in a public school in the city of Euclides da Cunha - Bahia, of a seventh class of elementary school II. After various stages of this research, it was proposed a literary reading notebook: the fable of the reader as a teaching materials built with the intention to provide the opportunity for contact with the literary text through activities in which the student is able to analyze, compare, combine, make inferences, and mainly extrapolations, linking these intellectual operations to the physical action and social practice, on the products. Methodologically this thesis into three chapters: in the first is in the debate on A. Rouxel reading methods, W.Cherry and C. Gomes, V.Aguiar, M. Bordini and R.Cosson; as the second chapter, was discussed collaboration and player training, the prospect of U. Eco and A.Rouxel; in the last chapter we took into consideration the topics of the action research methodology used in research and the results obtained in the investigation.